A Test of Chinese National Community Consciousness Based on the Anti-Japanese History of Guangdong and Hong Kong - Xinyi Luo (Studies in Social Science & Humanities, 2023)
As an important part of national social development, the Chinese national community consciousness is of high research value in today’s society. In this paper, the relationship between the Chinese national community and Chinese national community consciousness, the Chinese national community consciousness embodied in the war of resistance in Guangdong and Hong Kong, the importance of forging Chinese national community consciousness, and the methods of forging such consciousness are examined about to with concerning the history of the resistance in Guangdong and Hong Kong.